New Brunswick: Development of a Web-based orientation program and enhancing senior nurses' mentoring skills - Auffrey, Marise; Cormier-Daigle, Monique; Gagnon-Ouellette, Anne (Nursing Leadership, 2012)
This project to help new nurse recruits integrate into the hospital work environment had two components: the development of a new web-based orientation tool in French for new recruits and mentor training for more experienced nurses. The aim of the first component was to redesign delivery of the nursing orientation program by assessing individual needs of new recruits and developing "just in time" information sessions with online access and e-learning modules. The second component aimed to develop a voluntary mentorship training program for senior nurses that offered training on the role and responsibility of mentors. A total of 30 orientation modules were created as resources that could be adapted to the needs of each nursing unit and accessed online. Sixty nurse recruits used the programs. A mentor training program was developed, and 28 nurses were trained as mentors. The mentorship literature and guides, produced in French, will be a valuable resource for francophone nurses across Canada.

Life expectancy gap between the Francophone majority and Anglophone minority of a Canadian population - Auger, Nathalie; Harper, Sam; Barry, Amadou D.; Trempe, Normand; Daniel, Mark (European Journal of Epidemiology, 2012)
Language is an important determinant of health, but analyses of linguistic inequalities in mortality are scant, especially for Canadian linguistic groups with European roots. We evaluated the life expectancy gap between the Francophone majority and Anglophone minority of Québec, Canada, both over time and across major provincial areas. Arriaga’s method was used to estimate the age and cause of death groups contributing to changes in the life expectancy gap at birth between 1989–1993 and 2002–2006, and to evaluate patterns across major provincial areas (metropolitan Montréal, other metropolitan centres, and small cities/rural areas). Life expectancy at birth was greater for Anglophones, but the gap decreased over time by 1.3 years (52% decline) in men and 0.9 years (47% decline) in women, due to relatively sharper reductions in Francophone mortality from several causes, except lung cancer which countered reductions in women. The life expectancy gap in 2002–2006 was widest in other metropolitan centres (men 5.1 years, women 3.2 years), narrowest in small cities/rural areas (men 0.8 years, women 0.7 years), and tobacco-related causes were the main contributors. Only young Anglophones <40 years in small cities/rural areas had mortality higher than Francophones, resulting in a narrower gap in these areas. Differentials in life expectancy favouring Anglophones decreased over time, but varied across areas of Québec. Tobacco-related causes accounted for the majority of the current life expectancy gap.

Les inégalités sociales de santé chez les communautés francophones en situation minoritaire (CFSM) au Canada [numéro thématique] - Benoit, Monique; Bouchard, Louise; Garceau, Marie-Luce (Reflets, 2012)

La santé des francophones de l'Ontario. Un portrait régional tiré des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makvandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

L'offre active des services de santé en français en Ontario : une mesure d'équité - Bouchard, Louise; Beaulieu, Marielle; Desmeules, Martin (Reflets, 2012)
Cet article fait état d’une recherche sur l’offre active de services en français en Ontario. L’étude avait pour objectifs de recenser les définitions de l’offre active de services en français; d’identifier les pratiques d’offre active (facilitateurs ou obstacles); d’identifier les indicateurs de mesure de l’offre active et de proposer des recommandations permettant d’améliorer l’offre active de services en français. À cette fin, une revue documentaire, une enquête auprès de professionnels oeuvrant dans le domaine de la planification des services de santé en français ainsi qu’un atelier de cartographie conceptuelle ont été entrepris. Mots-clés : minorité linguistique, services de santé, offre active, Loi 8

Rapport d'enquête d'évaluation des besoins et de services de santé des francophones du Sud-Est - Bouchard, Louise; Gagnon-Arpin, Isabelle; Makvandi, E.wa (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)

Quel avenir pour les services sociaux et de santé des communautés anglophones du Québec ? - Carter, Jane (Déclin et enjeux des communautés de langue anglaise du Québec, 2012)

How healthy are Manitoba’s Francophones? A summary of report, Health and healthcare utilization of Francophones in Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Ottawa, Manitoba Center for Health Policy, 2012)
A summary of the report, Health and Healthcare Utilization of Francophones in Manitoba / La santé et l’utilisation des services de santé des francophones du Manitoba by Mariette Chartier, Greg Finlayson, Heather Prior, Kari-Lynne McGowan, Hui Chen, Janelle de Rocquigny, Randy Walld, Michael Gousseau Summary written by Michelle Houlden

Quel est l’état de santé des francophones du Manitoba ? Sommaire du rapport intitulé La santé et l'utilisation des services de santé des francophones du Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, University of Manitoba, 2012)

Health and healthcare utilization of Francophones in Manitoba - Chartier, Mariette; Finlayson, Gregory. S.; Prior, Heather. J.; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, 2012)

La santé et l'utilisation des services de santé des francophones du Manitoba - Chartier, Mariette; Finlayson, Gregory. S.; Prior, Heather. J.; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, 2012)

Portrait des minorités de langue officielle au Canada : les francophones de l’Île-du-Prince-Édouard - Chavez, Brigitte; Lepage, Jean-François; Bouchard-Coulombe, Camille (Statistique Canada, 2012)
Réalisé grâce au soutien financier du Secrétariat des langues officielles de Patrimoine canadien, de Ressources Humaines et Développement des Compétences Canada (RHDCC) ainsi que du ministère de la Justice Canada, ce portrait de la population de langue française de l’Île-du-Prince-Édouard est le dixième d’une série de portraits démolinguistiques des minorités de langue officielle au Canada rédigés par la Section des statistiques linguistiques de Statistique Canada. Cette étude brosse un portrait statistique général de la minorité de langue officielle de l’Île-du-Prince-Édouard en s’appuyant sur des données de recensements de la population ainsi que sur celles de l’Enquête sur la vitalité des minorités de langue officielle au Canada menée en 2006. Le but d’un tel portrait est de présenter un ensemble de caractéristiques, de comportements et de perceptions de la population de langue officielle minoritaire en mettant en évidence les possibilités d’analyse que recèlent les données. Le présent document ne se veut ni un simple assemblage de tableaux ni une étude approfondie de la dynamique démolinguistique de la population de langue française de l’Île-du-Prince-Édouard. Il présente une information diversifiée sur un ensemble de thèmes et de problématiques qui revêtent un intérêt pour les minorités de langue officielle et pour quiconque s’intéresse à la situation passée, actuelle et future des populations de langue officielle en situation minoritaire au Canada. La première section de ce portrait démolinguistique porte sur le choix des critères de définition de la population de langue française de l’Île-du-Prince-Édouard qui seront utilisés aux fins de ce document ainsi que sur une brève description des sources de données utilisées. La seconde section présente différentes informations qui rendent compte de l’évolution de la population de langue française ainsi que sur la répartition et la concentration de cette population sur le territoire de l’Île-du-Prince-Édouard. Cette information est accompagnée d’une carte géographique présentée en annexe et d’un tableau détaillé sur l’effectif, le poids relatif et la répartition de la population de langue française de l’Île. La troisième section de ce portrait porte sur les principaux facteurs qui influent sur l’évolution de la population de langue française dans cette province ou qui en résultent, soit la transmission de la langue maternelle et l’effet de l’exogamie, la structure par âge, la mobilité linguistique intragénérationnelle et la migration interprovinciale. De plus, on y présente de l’information sur l’usage du français dans la sphère publique et sur l’évolution de la capacité de soutenir une conversation selon le groupe de langue maternelle. La quatrième section porte sur quelques secteurs clés pour la vitalité des communautés de langue officielle en situation minoritaire tels qu’identifiés dans la Feuille de route pour la dualité linguistique canadienne 2008-2013 : agir pour l’avenir1, soit la santé, la justice, l’éducation et les médias, les arts et la culture. Nous y présentons également des statistiques sur la participation communautaire, les caractéristiques de l’emploi et du revenu ainsi que sur l’utilisation du français au travail. Finalement, la dernière section de ce portrait présente des statistiques sur l’appartenance identitaire des francophones et leurs perceptions à l’égard de la présence du français dans leur communauté, de l’offre de services en français de la part du gouvernement fédéral, du respect des droits linguistiques ainsi qu’à l’égard du fait que des gens travaillent au développement de la communauté francophone.

Portrait of Official-Language Minorities in Canada: Francophones in Prince Edward Island - Chavez, Brigitte; Lepage, Jean-François; Bouchard-Coulombe, Camille (Statistics Canada, 2012)
This demolinguistic portrait of the French-speaking population in Prince Edward Island was undertaken with the financial support of Canadian Heritage’s Official Languages Secretariat, Human Resources and Skills Development Canada (HRSDC) and Justice Canada. It is the tenth in a series of demolinguistic portraits of official-language minorities in Canada, prepared by Statistics Canada’s Language Statistics Section. This study paints a general statistical portrait of the official-language minority in Prince Edward Island based on data from the Census of Population and the Survey on the Vitality of Official-Language Minorities in Canada, conducted in 2006. The purpose of such a portrait is to present a set of characteristics, behaviours and perceptions of the minority official-language population, exploiting the analytical opportunities contained in the data. This document is intended to be neither a mere collection of tables nor an in-depth study of the demolinguistic dynamics of the English-speaking population in Prince Edward Island. It presents a range of themes and issues that will be of interest to official-language minorities and anyone concerned with the past, present and future situation of minority official-language populations in Canada. Section 1 of this demolinguistic portrait concerns the criteria chosen in this study to define Prince Edward Island’s French-speaking population. It also provides a brief description of the data sources used. Section 2 presents varied information on the evolution of the French-speaking population and its geographic distribution and concentration in Prince Edward Island. This includes an appended map and a detailed table on the size, relative weight and distribution of the Island’s French-speaking population. Section 3 concerns the main factors that affect or are affected by changes over time in this province’s French-speaking population: transmission of mother tongue and the effect of exogamy; age structure; intragenerational linguistic mobility; and interprovincial migration. It also discusses the use of French in the public sphere and how the ability to conduct a conversation in that language has evolved according to mother-tongue group. Section 4 looks at a few sectors essential to the vitality of minority official-language communities, as identified in the Roadmap for Canada’s Linguistic Duality 2008–2013: Acting for the Future,1 namely health, justice, education and the media, the arts and culture. It also provides statistics on community participation, employment and income characteristics, and the use of French at work. The last section of this portrait presents statistics on the identity of Francophones and their perceptions regarding the presence of French in their community, the provision of federal government services in French, the respect for linguistic rights, and the fact that people are working to develop the Francophone community.

Quel avenir pour le projet autonomiste des communautés francophones en situation minoritaire ? Réflexion sur les politiques publiques canadiennes en matière de langues officielles - Chouinard, Stéphanie (Minorités linguistiques et société, 2012)
Nous tentons de mettre au jour quelques possibilités d’application, en matière de politiques publiques, des revendications de reconnaissance politique des communautés francophones en situation minoritaire (CFSM) du Canada, que nous organisons selon deux optiques différentes, soit l’autonomie et l’intégration. Après quelques considérations d’ordre sociopolitique et juridique, nous plaiderons pour une asymétrie dans l’élaboration des politiques publiques relatives à ces communautés. Nous soulignerons aussi le poids des enjeux de pouvoir dans la relation entre l’État et les CFSM, notamment sur le plan de la gouvernance, dans l’élaboration de ces politiques. Mots-clés : autonomie, politiques publiques, communautés francophones en situation minoritaire, communautés de langue officielle au Canada, participation politique

Agir ! Pour ma santé : une intervention harmonisant Services médicaux et diagnostiques et services communautaires pour les Franco-Manitobains souffrant de dépression - de Moissac, Danielle; Bohémier, Moniqu; Herdman, Chelsea; Roch-Gagné, Margaux; Paillé, Julie; Johnston, Christine; Arpin-Molinski, Michelle; Dupuis, Georgette; Saint-Hilaire, Mélanie; Prairie, Liliane (Reflets, 2012)

Défis associés à l’offre de services de santé et de services sociaux en français au Manitoba : perceptions des professionnels - de Moissac, Danielle; de Rocquigny, Janelle; Giasson, Florette; Tremblay, Cindy-Lynne; Aubin, Natalie; Charron, Marc; Allaire, Gratien (Reflets, 2012)
Les services de santé et les services sociaux en français ne sont accessibles qu’auprès d’un quart de la population francophone au Manitoba (de Moissac, 2011). Une pénurie de professionnels pouvant offrir des services en français est perçue comme un obstacle important pour les usagers qui recherchent ces services et pour les professionnels qui voudraient assurer un suivi en français pour leurs clients. Une hésitation à s’identifier comme francophone et un manque de connaissance des ressources disponibles en français contribuent-ils à cette perception de pénurie? Cet article traite des défis entourant l’offre de services de santé et de services sociaux en français au Manitoba et suggère des pistes de solutions. Mots-clés : disponibilité, accessibilité, minorité francophone, Manitoba, professionnels

Le statut socioéconomique des anglophones du Québec : ceux qui sont partis et ceux qui sont restés - Floch, William; Pocock, Joanne (Déclin et enjeux des communautés de langue anglaise du Québec, 2012)

Linguistic variables: A necessity for health services planning tailored to the needs of Francophones. Current Status - French Language Heatlh Services Network of Eastern Ontario (Current Status, 2012)

Examining the geographic distribution of French-speaking physicians in Ontario - Gauthier Alain P.; Timony Patrick E.; Wenghofer, Elizabeth. F. (Canadian Family Physician, 2012)
Abstract: Objective: To determine how many physicians in Ontario express a proficiency in providing services in the French language, and to assess the geographic distribution of such physicians. Design: Population-based analysis of the 2007 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. Setting: Ontario. Participants: A total of 22688 GPs, FPs, and other specialists certified by the College of Family Physicians of Canada and the Royal College of Physicians and Surgeons of Canada who responded to the survey. Main outcome measures: First official language spoken and languages of competency to conduct practice. Results: The physician-to-patient ratio by first official language spoken is 1 physician per 138 Francophone patients in Ontario. There is 1 French-speaking GP or FP for every 297 Francophone patients, and most French-speaking physicians are located in southern Ontario (91.4%), at a ratio of 1 physician per 111 Francophone patients. The most promising French-speaking physician–to–Francophone patient ratios are found in southern Ontario (1:248 for GPs and FPs, and 1:202 for other specialists) and in urban Ontario (1:266 for GPs and FPs, and 1:209 for other specialists). Conclusion: Clearly, there is a promising number of physicians, relative to the amount of French-speaking residents in Ontario, who identified a competency in offering services in French. However, while the number of physicians who indicated a self-assessed competency to deliver health services in French is promising, it is the maldistribution of such services that is of concern. Thus, efforts must be made to attract French-speaking physicians to areas where there is the greatest demand, particularly in the northern part of the province. Résumé Objectif: Déterminer combien de médecins ontariens se disent compétents pour fournir, des services en français et vérifier la distribution géographique de ces médecins. Type d’étude: Analyse démographique du rapport de 2007 sur la réinscription annuelle à l’Ordre des médecins et chirurgiens de l’Ontario. Contexte: L’Ontario. Participants: Un total de 22 688 omnipraticiens (OP), MF et autres spécialistes diplômés du Collège des médecins de famille du Canada et du Collège royal des médecins et chirurgiens du Canada qui ont répondu à l’enquête. Principaux paramètres à l’étude: Première langue officielle parlée et langues de compétence pour la pratique. Résultats: En Ontario, le rapport médecin/patient dans le cas de la première langue officielle parlée est de 1 médecin pour 138 patients francophones. On compte un OP ou MF francophone pour 297 patients francophones et les médecins francophones sont localisés pour la plupart (91,4%) dans le sud de l’Ontario, où on observe 1 médecin pour 111 patients francophones. C’est dans le sud de l’Ontario que le rapport médecin francophone/patient francophone est le plus favorable (1/248 pour les OP et les MF, et 1/1202 pour les autres spécialistes) et dans les milieux urbains (1/266 pour les OP et les MF et 1/1209 pour les autres spécialistes). Conclusion: Il est certain qu’en Ontario, il y a un nombre encourageant de médecins qui, par rapport au nombre de résidents francophones, se sont dits compétents pour offrir des services en français. Malgré ce rapport favorable, c’est la mauvaise distribution de ces services qui est préoccupante. Il faudrait donc s’efforcer d’attirer des médecins francophones dans les régions où la demande est la plus forte, notamment dans le nord de la province.

Compétences linguistiques et qualité de services. Argumentaire pour des services de soins de santé en français de qualité - Gauthier, Hubert; Reid, Marc-André (Conseil communauté en santé en français du Manitoba, 2012)

Autonomie culturelle, cultures sociétales et vitalité des communautés de langue officielle en situation minoritaire au Canada - Landry, Rodrigue (Minorités linguistiques et société, 2012)
Partant d’un modèle macroscopique des facteurs associés à la vitalité d’une minorité linguistique en situation intergroupe, cet article présente cinq principes expliquant comment les structures sociales s’imposent sur les vécus langagiers des membres de la minorité. Ce même modèle montre comment tant les individus que la collectivité peuvent exercer leur autonomie langagière pour contrer ce déterminisme social. Le modèle de l’autonomie culturelle est explicité et appliqué aux communautés de langue officielle en situation minoritaire (CLOSM) dans le but de faire valoir leur besoin d’autonomie institutionnelle pour assurer leur vitalité au Canada. La reconnaissance du droit à l’autonomie culturelle pourrait être un mode de légitimation des droits propres à ces communautés. Les CLOSM sont décrites comme des prolongements des deux cultures sociétales qui constituent le fondement de la dualité linguistique canadienne. Mots-clés : autonomie culturelle, culture sociétale, vitalité linguistique, droits linguistiques, minorités linguistiques

Is Francophone language status associated with diffences in the health services use of rural Nova Scotians? - Langille, Donald; Rainham, Daniel; Kisely, Steve (Canadian Journal of Public Health, 2012)
L’étude a pour objet de vérifier empiriquement la validité d’un modèle théorique qui propose un système de relations liant la construction de l’identité ethnolinguistique à la satisfaction de vie, un aspect du mieux-être psychologique, et à l’autoévaluation de sa santé. Un échantillon de 8 124 élèves du secondaire, provenant de 30 conseils scolaires francophones situés à l’extérieur du Québec, a participé à l’étude. Les résultats sont conformes au modèle fondé sur la théorie de l’autodétermination, qui stipule que lorsque la construction identitaire se fait dans un contexte d’appui à des besoins psychologiques de base, elle est reliée au mieux-être psychologique de la personne. Abstract

Portrait des minorités de langue officielle au Canada : les francophones du Manitoba - Lepage, Jean-François; Bouchard-Coulombe, Camille; Chavez, Brigitte (Statistique Canada, 2012)
Réalisé grâce au soutien financier du Secrétariat des langues officielles de Patrimoine canadien, de Ressources Humaines et Développement des Compétences Canada (RHDCC) ainsi que du ministère de la Justice Canada, ce portrait de la population de langue française du Manitoba est le huitième d’une série de portraits démolinguistiques des minorités de langue officielle au Canada rédigés par la Section des statistiques linguistiques de Statistique Canada. Cette étude brosse un portrait statistique général de la minorité de langue officielle du Manitoba en s’appuyant sur des données de recensements de la population ainsi que sur celles de l’Enquête sur la vitalité des minorités de langue officielle au Canada menée en 2006. Le but d’un tel portrait est de présenter un ensemble de caractéristiques, de comportements et de perceptions de la population de langue officielle minoritaire en mettant en évidence les possibilités d’analyse que recèlent les données. Le présent document ne se veut ni un simple assemblage de tableaux ni une étude approfondie de la dynamique démolinguistique de la population de langue française au Manitoba. Il présente une information diversifiée sur un ensemble de thèmes et de problématiques qui revêtent un intérêt pour les minorités de langue officielle et pour quiconque s’intéresse à la situation passée, actuelle et future des populations de langue officielle en situation minoritaire au Canada. La première section de ce portrait démolinguistique porte sur le choix des critères de définition de la population de langue française au Manitoba qui seront utilisés aux fins de ce document ainsi que sur une brève description des sources de données utilisées. La seconde section présente différentes informations qui rendent compte de l’évolution de la population de langue française ainsi que sur la répartition et la concentration de cette population sur le territoire manitobain. Cette information est accompagnée d’une série de cartes géographiques présentée en annexe et d’un tableau détaillé sur l’effectif, le poids relatif et la répartition de la population de langue française au Manitoba. La troisième partie de ce portrait porte sur les principaux facteurs qui influent sur l’évolution de la population de langue française dans cette province ou qui en résultent, soit la fécondité, la transmission de la langue maternelle et l’effet de l’exogamie, la structure par âge, la mobilité linguistique intragénérationnelle, la migration interprovinciale et internationale. De plus, on y présente de l’information sur l’usage du français dans la sphère publique et sur l’évolution de la capacité de soutenir une conversation selon le groupe de langue maternelle. La quatrième partie porte sur quelques secteurs clés pour la vitalité des communautés de langue officielle en situation minoritaire tels qu’identifiés dans la Feuille de route pour la dualité linguistique canadienne 2008-2013 : agir pour l’avenir1, soit la santé, la justice, l’éducation et les médias, les arts et la culture. Nous y présentons également des statistiques sur la participation communautaire, les caractéristiques de l’emploi et du revenu ainsi que sur l’utilisation du français au travail. Finalement, la dernière partie de ce portrait présente des statistiques sur l’appartenance identitaire des francophones et leurs perceptions à l’égard de la présence du français dans leur communauté, de l’offre de services en français de la part du gouvernement fédéral, du respect des droits linguistiques ainsi qu’à l’égard du fait que des gens travaillent au développement de la communauté francophone.

Portrait of Official-Language Minorities in Canada: Francophones in Manitoba - Lepage, Jean-François; Bouchard-Coulombe, Camille; Chavez, Brigitte (Statistics Canada, 2012)
This demolinguistic portrait of the French-speaking population in Manitoba was undertaken with the financial support of Canadian Heritage’s Official Languages Secretariat, Human Resources and Skills Development Canada (HRSDC) and Justice Canada. It is the eighth in a series of demolinguistic portraits of official-language minorities in Canada, prepared by Statistics Canada’s Language Statistics Section. This study paints a general statistical portrait of the official-language minority in Manitoba based on data from the Census of Population and the Survey on the Vitality of Official-Language Minorities in Canada, conducted in 2006. The purpose of such a portrait is to present a set of characteristics, behaviours and perceptions of the official-language minority population, exploiting the analytical opportunities contained in the data. This document is intended to be neither a mere collection of tables nor an in-depth study of the demolinguistic dynamics of the French-speaking population in Manitoba. It presents a range of information on themes and issues that will interest official-language minorities and anyone concerned with the past, present and future situation of official-language minority populations in Canada. Section 1 of this demolinguistic portrait concerns the criteria used in this study to define the French-speaking population in Manitoba. It also provides a brief description of the data sources used. Section 2 presents varied information on the evolution of the French-speaking population and its geographic distribution and concentration in Manitoba. This information includes a series of appended maps and a detailed table on the size, relative weight and distribution of the French-speaking population in Manitoba. Section 3 concerns the main factors that affect or are affected by changes over time in this province’s French-speaking population: fertility; transmission of mother tongue and effect of exogamy; age structure; intragenerational linguistic mobility; and interprovincial and international migration. It also discusses the use of French in the public sphere and how the ability to conduct a conversation in that language has evolved according to mother-tongue group. Section 4 looks at a few sectors essential to the vitality of official-language minority communities, as identified in the Roadmap for Canada’s Linguistic Duality 2008–2013: Acting for the Future1: health; justice; education; and the media, arts and culture. It also provides statistics on community participation, employment and income characteristics, and the use of French at work. The last section of this portrait presents statistics on the identity of Francophones and their perceptions regarding the presence of French in their community, the provision of federal government services in French, the respect for linguistic rights, and the fact that people are working to develop the Francophone community.

Reference framework: Training for active offer of French-language health services - Lortie, L.ise; Lalonde, André. J. (Consortium national de formation en santé, 2012)

Cadre de référence pour la formation à l’offre active des services de santé en français (n°978-0-9879240-1-8) - Lortie, Lise; Lalonde, André. J. (Consortium national de formation en santé, 2012)

La situation socioéconomique des anglophones du Québec - Lussier, Marie-Hélène (Institut national de santé publique du Québec, 2012)

The socioeconomics status of Anglophones in Québec - Lussier, Marie-Hélène (Institut national de santé publique du Québec, 2012)

Language barriers: Use of regular medical doctors by Canada's official language minorities - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda, R.; Musto, Richard; King-Shier, Kathryn M.; Quan, Hude (Canadian Family Physician, 2012)

Experiences of French speaking immigrants and non-immigrants accessing health care services in a large Canadian city - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda. R.; Musto, Richard; Quan, Hude; King-Shier, Kathryn. M. (International Journal of Environmental Research and Public Health, 2012)
French speakers residing in predominantly English-speaking communities have been linked to difficulties accessing health care. This study examined health care access experiences of immigrants and non-immigrants who self-identify as Francophone or French speakers in a mainly English speaking province of Canada. We used semi-structured interviews to gather opinions of recent users of physician and hospital services (N = 26). Language barriers and difficulties finding family doctors were experienced by both French speaking immigrants and non-immigrants alike. This was exacerbated by a general preference for health services in French and less interest in using language interpreters during a medical consultation. Some participants experienced emotional distress, were discontent with care received, often delayed seeking care due to language barriers. Recent immigrants identified lack of insurance coverage for drugs, transportation difficulties and limited knowledge of the healthcare system as major detractors to achieving health. This study provided the groundwork for future research on health issues of official language minorities in Canada. Keywords: immigrants; French language; health care access; family doctor; qualitative descriptive; official language minorities

Les variables linguistiques : un impératif pour une planification de services de santé adaptée aux besoins des francophones. État des lieux - Réseau des services de santé en français de l’Est de l’Ontario (État des lieux, 2012)

Étude sur les services de santé linguistiquement et culturellement adaptés : portrait pancanadien - Tremblay, Suzanne (Société Santé et Mieux-être en français du Nouveau-Brunswick, Société Santé en français et Santé Canada, 2012)

Study on linguistically and culturally adapted healths services: A pan-Canadian portrait - Tremblay, Suzanne (Société Santé et Mieux-être en français du Nouveau-Brunswick, Société Santé en français & Health Canada, 2012)

Assessment of validity for the “language spoken at home” variable in Québec death records: Summary. Language, determinant of health status and of services' quality - Trempe, Normand; Boivin, Marie-Claude; Lo, Ernest; Diogo Barry, Amado (Institut national de santé publique du Québec, 2012)

La validité de la variable « Langue d’usage à la maison » du Fichier des décès du Québec : synthèse. La langue, déterminant de l'état de santé et de la qualité des services - Trempe, Normand; Boivin, marie-claude; Lo, Ernest; Diogo Barry, Amado (Institut national de santé publique du Québec, 2012)

Comparing the rates of mental disorders among different linguistic groups in a representative Canadian population - Vasiliadis, Helen-Maria; Lepnurm, Marje; Tempier, Raymond; Kovess-Masfety, Viviane (Social psychiatry and psychiatric epidemiology, 2012)
Purpose We aimed to determine whether linguistic group influences reported prevalence rates for a number of common mental disorders. Methods Secondary data analyses of the Canadian Community Health Survey cycle 1.2 (CCHS 1.2) were carried out on representative bilingual French and English, monolingual French and English and other language groups in Canada. Past year prevalence of major depression, anxiety disorders (agoraphobia, social phobia, panic disorder) and alcohol abuse/dependence were ascertained using versions of the World Mental Health Composite International Diagnostic Interview (WMH-CIDI) questionnaire. Multivariate data analyses were used to model past year presence of a mental disorder as a function of linguistic group, defined as languages can converse in, and adjusting for socioeconomic, demographic and cultural factors. Results Overall, past year rates for the presence of a common mental disorder were 10.7% (9.7–11.7%) for the bilingual English; 9.0% (8.1–9.9%) for the bilingual French; 10.2% (9.8–10.6) for the monolingual English; 8.5% (7.7–9.3%) for the monolingual French; and 8.3% (6.1–10.4%) for the other language group. After adjusting for a number of socio-demographic, economic and cultural factors, the multivariate analyses showed that the linguistic groups were equally likely to report the presence of a past year common mental disorder. This was also true for comparisons between the bilingual participants responding in French and English. Conclusions The differences observed in the reported crude rates for the presence of mental disorders across the different linguistic groups in Canada were explained by socio-demographic, economic, and factors such as immigration, spoke a third language and province of residence, and not explained by language of interview.

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the  increase  in  international  mobility,  healthcare  systems  should  no  longer  be  ignoring  language  barriers.  In  addition  to  the  benefit  of  reducing  long‐term  costs,  immigrant‐friendly  organizations  should  be  concerned  with  mitigating  the  way  language  barriers  increase  individuals’  social  vulnerabilities  and  inequities  in  health  care  and  health  status.  This  paper  reports  the  findings  of  a  qualitative,  exploratory  study  of  the  health  literacy  of  28  Francophone  families  living  in  a  linguistic‐minority  situation  in  Canada.  Analysis  of  interviews  revealed  that  participants’  social  vulnerability,  mainly  due  to  their  limited  social  and  informational  networks,  influenced  the  construction  of  family  health  literacy.  Disparities  in  access  to  healthcare  services  could  be  decreased  by  having  health  professionals’  work  in  alliance  with  Francophone  community  groups  and  by  hiring  bilingual  health  professionals.  Linguistic  isolation  and  lack  of  knowledge  about  local  cultural  organizations  among  Francophone immigrants  were  two  important  findings  of  this  study.